Visibility : the seeing of near and distant landscape features - Malm, William C. (Elsevier Science, 2016)
Visibility: The Seeing of Near and Distant Landscape Features reviews the science of visibility from how to measure it quantitatively to its impacts by one of the foremost experts in the field. Carefully designed pedagogy allows a diversity of readers, from regulators to researchers to use this book to further their understanding of the field. Topics covered include the interaction of light with the atmosphere and aerosols, the transfer of light through the atmosphere especially as it relates to non-uniform haze layers, perception questions, including visibility metrics, image processing techniques for purposes of visually displaying effects of haze on scenic landscapes, visibility monitoring techniques, and the history of visibility regulatory development.